Ultrasonography-guided corticosteroid injection in the coracohumeral ligament in patients with adhesive capsulitis of the shoulder: a double-blinded, sham-controlled randomized study - Singh, Harpreet; Rathore, Lakhan Pratap Singh; Salimath, Suman; Makhija, Meena; Phadke, Vandana (Journal of shoulder and elbow surgery, 2024)
Contracture and thickening of the coracohumeral ligament (CHL) occur in patients with adhesive capsulitis. This adversely affects the movement and function of the shoulder joint. There is limited evidence that explores the effectiveness of an isolated steroid injection into the CHL in combination with physical therapy. This prospective randomized control trial aimed to evaluate the clinical effects of ultrasonography-guided corticosteroid injection compared to a sham injection into the CHL in subjects with adhesive capsulitis. Forty patients (23 males, 52.2 ± 8 years of age) with unilateral adhesive capsulitis (with 5.4 ± 2 months’ mean duration of symptoms) were randomly assigned to either the experimental or control group. Both groups received ultrasonography-guided injections into the CHL. The experimental group (n = 20) received corticosteroids and the control group (n = 20) received a sham lidocaine injection. All subjects underwent supervised conventional physical therapy 3 times a week for 3 months. Subjects were evaluated for improvements in pain, range of motion, and disability at 6 and 12 weeks compared with preinjection baseline measurements. Data were compared statistically across groups and times at P < .05. The CHL thickness was compared at baseline across sides using paired t tests. The experimental group showed statistically greater improvements in pain, functional scores, flexion, abduction, and internal and external rotation range of motion at 12 weeks compared with the control group. Pain reduction was observed in both groups at 6 and 12 weeks, but the experimental group exhibited significantly greater reductions. The CHL was significantly thicker on the affected side than on the unaffected side (P < .001). This study partially supported the hypothesis. Notably, significant improvements in pain, range of motion, and functional scores were observed at 12 weeks in the experimental group. The greater improvements in pain and external rotation may have resulted in lower disability scores in the experimental group. The results emphasize the importance of targeted intervention into the CHL.